Myeloma impairs mature osteoblast function but causes early expansion of osteo‐progenitors: temporal changes in bone physiology and gene expression in the KMS12BM model. (2nd November 2015) - Kassen, Deepika; Lath, Darren; Lach, Anna; Evans, Holly; Chantry, Andy; Rabin, Neil; Croucher, Peter; Yong, Kwee L.
Summary: Myeloma bone disease results from an uncoupling of osteoclastic resorption and osteoblastic bone formation, but early changes in osteogenic function remain poorly defined. We used the KMS12BM xenograft model to investigate cellular and molecular events at early and late stages of disease. Lytic lesions and changes in osteoblast and osteoclast numbers occur late (8 weeks), however, micro‐computed tomography of femora revealed significant reduction in bone volume at earlier disease stages (3 weeks) when tumour burden is low. Calcein labelling demonstrated reduced mineralization and bone formation at 3 weeks, suggesting functional impairment despite preserved osteoblast numbers. Osteo‐progenitors from compact bone increased early (1 week), but fell at 3 weeks and were profoundly suppressed by 8 weeks. Exposure of osteoblast progenitors to multiple myeloma (MM) cells in vitro induced cell cycling, suggesting a mechanistic basis for early expansion of osteo‐progenitors. We observed temporal changes in chemokine, osteogenic and osteoclastogenic genes in the stromal compartment. Notably, an early rise in CCL3 may underlie functional changes in mature osteoblasts at 3 weeks. Our data indicate that MM has distinct effects on mature osteoblasts and immature osteo‐progenitors. Our findings argue for early clinical intervention to prevent bone changes that ultimately lead to the development of osteolytic disease.